SAT0674 Early treatment response to conventional dmard therapy in rheumatoid arthritis is a better predictor of low disease activity or treatment escalation at 12 and 24 months than autoantibodies or erosions. (15th June 2017) - Richter, A; Strangfeld, A; Herzer, P; Kaufmann, J; Klopsch, T; Zinke, S; Listing, J; Zink, A
Abstract : Background: The EULAR guidelines recommend using the presence of seropositivity or erosions to support treatment decisions. The prognostic value of these factors regarding the primary treatment target in rheumatoid arthritis, remission or low disease activity (LDA), is unclear. Objectives: To investigate biomarkers, csDMARD treatments and response to treatment regarding their usefulness to predict LDA or the need to escalate treatment within 24 month. Methods: The control group in RABBIT (R heumatoid A rthritis: Ob servation of bi ologic t herapy) comprises N=2, 228 patients who were enrolled at treatment start with conventional-synthetic (cs)DMARDs after failure of at least one csDMARD therapy, mostly methotrexate (MTX) monotherapy. We excluded patients with a DAS28-ESR<3.2 at enrollment and those with ≥2 csDMARD failures (n=618). 102 patients were excluded due to enrollment less than 12 month prior to closure of the data base (April 30th, 2016). The DAS28-ESR, physical function, age, seropositivity (RF+/ACPA+), comorbidities (≥3 vs. <3) and the presence of erosions at baseline were evaluated as prognostic factors. Concomitant treatment with glucocorticoids (mg/d) and csDMARDs, response to treatment (3–6 month after enrollment) were additionally examined. We applied a multinomial generalized-estimating-equation (GEE) model to investigate: (1) achievement of LDA at month 12/24 or (2) treatment escalation (biologic treatment) in year one and two after enrollment. Results: More than one third of patients (34.2%) were treated with a combination of MTX and leflunomide (LEF), 23.6% with LEF mono, 20.8% with MTX + hydroxychloroquine (HCQ) or sulfasalazine (SSZ), 16.5% with MTX mono, and 4.9% with SSZ mono. We found no major differences across treatment regimens except for patients treated with MTX+HCQ who had a lower DAS28, better physical function and shorter disease duration at treatment start. Significant predictors for achieving LDA were low DAS28 at baseline, improvement in DAS28 within 3–6 month, better physical function and less than 3 comorbidities (table). Escalation to bDMARD therapy was significantly more frequent in younger patients, those with no improvement in DAS28 or concomitant glucocorticoid treatment, and in patients with less than 3 comorbidities. There were no differences between treatments regarding achievement of LDA. However, switching to bDMARDs was most frequent in patients treated with LEF mono or with LEF+MTX. The presence of erosions or seropositivity were not associated with any of the outcomes (table). Conclusions: The highest impact on achieving LDA was found in disease activity at baseline and response to treatment within 3–6 month. The relevance of erosions and/or seropositivity regarding the prediction of a poorer outcome is disputable. Acknowledements: RABBIT is supported by a joint, unconditional grant from AbbVie, Bristol-Myers Squibb, Celltrion, MSD Sharp & Dohme, Pfizer, Roche, Samsung Bioepis and UCB. Disclosure of Interest: A. Richter Consultant for: Pfizer, A. Strangfeld Speakers bureau: BMS, MSD, Pfizer, Roche, Sanofi-Aventis, P. Herzer Consultant for: AbbVie, Pfizer, J. Kaufmann: None declared, T. Klopsch: None declared, S. Zinke: None declared, J. Listing Consultant for: Sandoz, Pfizer, A. Zink Speakers bureau: AbbVie, BMS, MSD, Pfizer, Roche, UCB